The Utilization of Prebiotics, Probiotics, Organic Acids and Antibiotics in Monogastric Animals - Biagi, Giacomo; Vecchiato, C.G.; Pinna, C. (KnE Life Sciences, 2017)
The gastrointestinal microbiota is a complex ecosystem made up of a multitude of bacterial species, some of which are potentially pathogenic, while others are considered good for the host. The beneficial microorganisms that live in the hindgut influence gastrointestinal functionality and the host’s health in general. Nowadays, many dietary supplements are available to be fed to young farm animals such as broilers, turkeys, piglets and calves in order to improve their intestinal health and growth performance. Despite the fact that non-pharmacological feed additives in general do not reach the efficacy of antibiotics as growth promoters, the proper choice and use of a dietary supplement may improve livestock productivity. Nevertheless, it has to be considered that dietary supplements usually increase the feed price, which means that the cost-benefit ratio of feed additives should always be determined. Keywords: gastrointestinal microbiota; dietary supplements; livestock productivity